Intersectionalities, rights and policies - Vieira, Miriam Steffen (2021)
The notion of intersectionalities emerges from the political experience of black feminisms and guides the intersecting dynamics that underlie social inequalities such as gender, race, sexualities and class. Therefore, it is taken as a possibility to produce theory and to analytically question different experiences and contexts, generating new lessons about the processes of domination. In addition to being a central methodological tool, in the experiences and political actions, it presents itself as an open field of resistance to Western hegemonic narratives and practices. In this text, we present the articles that make up the Intersectionalities, rights and policies dossier. With attention to the diversity of approaches and contributions that allow expanding the density of epistemological foundations in social sciences, as in political praxis.